Complicações e qualidade de vida em pacientes submetidas a biopsia de linfonodo sentinela ou a linfadenectomia axilar no câncer de mama - Carolina Rodrigues Paim (2007)
This study aimed to investigated quality of life (QoL) and pos lymphadenectomy complications and their association among women who had axillary lymph node dissection or sentinel node biopsy, and to validate the Brazilian Portuguese version of the questionnaire FACT-B (version 4). 96 women were divided in two groups: Group I (n = 48): sentinel node biopsy, and Group II (n = 48) :axillary lymph node dissection. Data were collected using (1) Protocol for clinical evaluation (2) Patients file (3) Questionnaire to evaluate pain (McGill Pain- Short-Form), and (4) Questionnaire to evaluate QoL (FACTB). Results: pain was more frequent in Group I (31/48) than in Group II (24/48) (p=0.0027). There were not significant differences on sensitivity changes, reduction on shoulder strength, and limitation of shoulder movement. Lymphedema had larger frequency on Group I (14/48) than on Group II (2/48) (p=0.0027). There was not cases of winged scapula in Group II, but four cases in Group I (p<0.05). There were not significant differences onnumber of dissected lymp nodes and frequency of complications. FACT-B had a Mean of 101 (SD=33) in Group II, and of 95.4 (SD=21) in Group I, but no significant difference. There was not significant difference on pain between the groups, neither (QoL) and lymphedema and change on sensitivity. There was a moderate correlation between QoL andshoulder flexion mobility (p=0.02). Correlation between QoL and diminished should flexion muscular strength was -0.4, and -0.5 for shoulder abduction (p<0.001). Correlation between pain and quality of life was significant (r=-0.53, p<0,001). In conclusion, Group II presented less frequency of pos lymphadenectomy complications than Group I. There was not significant difference on QoL between the two groups. There was significant differences between QoL and pain, mobility limitations and diminished strength of shoulder and arm. The Brazilian Portuguese translation of FACT-B (version 4) was reliable and valid in thisstudy. Key-words: axillary lymph node, breast cancer, pos lymphadenectomy complications, quality of life, sentinel node biopsy